The Correlation of Effective Sentence Mastery and Language Attitude with Students' Writing Summary Ability - Sri Lestari; Surastina Surastina; Frieska Maryova Rachmasisca; Tommy Hastomo (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
The purpose of this study was to analyze the relationship between (1) practical sentence mastery and summary writing ability, (2) language attitude and summary writing ability, and (3) practical sentence mastery and language attitude together with summary writing skills. The research used is the correlational method. The population of this study was students of class VIII Even Semester SMP Negeri 1 Bumi Agung, Way Kanan Regency, 2017/2018 Academic Year. There are 61 people as research samples in this study. The analytical technique used is statistical regression and correlation techniques. The finding shows that language has a significant relationship with the ability to write a summary with a correlation coefficient of 0.693, and mastery of effective sentences and language attitudes have a significant relationship with the students' writing summary with a correlation coefficient of 0.733.